2010
DOI: 10.1111/j.1570-7458.2010.01085.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spinosad and predatory mites on control of Frankliniella occidentalis in three strawberry cultivars

Abstract: Western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae), is a major pest of strawberry, Fragaria · ananassa Duchesne (Rosaceae). Spinosad is highly efficacious against F. occidentalis, and spinosad is believed to be compatible in an integrated pest management program. This study determined whether F. occidentalis could be controlled with predatory mites [Typhlodromips montdorensis (Schicha), Neoseiulus cucumeris (Oudemans) (both Acari: Phytoseiidae), and Hypoaspis miles (Berlese)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Stratiolaelaos scimitus Berlese (formerly known as Hypoaspis miles Womersley) (Acari: Laelapidae) is being produced commercially for control of glasshouse sciarids (Jess & Kilpatrick, 2000;Wright & Chambers, 1994) and F. occidentalis (Berndt, Meyhofer, & Poehling, 2004;Rahman, Broughton, & Spafford, 2011;Thoeming & Poehling, 2006). Although the potential value of S. scimitus has been tested abroad, this indigenous species in China has not yet been extensively studied and applied (Wang et al, 2009;Wang, Liu, et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Stratiolaelaos scimitus Berlese (formerly known as Hypoaspis miles Womersley) (Acari: Laelapidae) is being produced commercially for control of glasshouse sciarids (Jess & Kilpatrick, 2000;Wright & Chambers, 1994) and F. occidentalis (Berndt, Meyhofer, & Poehling, 2004;Rahman, Broughton, & Spafford, 2011;Thoeming & Poehling, 2006). Although the potential value of S. scimitus has been tested abroad, this indigenous species in China has not yet been extensively studied and applied (Wang et al, 2009;Wang, Liu, et al, 2010).…”
Section: Introductionmentioning
confidence: 97%
“…In the laboratory, the numbers of thrips adults and larvae, T. montdorensis and N. cucumeris in each flower and fruit were counted and averaged per flower or fruit. As a result of the difficulty of sampling of H. miles in our previous study (Rahman et al., 2011a), no attempt was made to count H. miles .…”
Section: Methodsmentioning
confidence: 97%
“…The third mite, H. miles , is a soil‐dweller that predates on the prepupal and pupal stages (Glockemann, 1992), although Berndt (2003) suggests that it may also prey on late second instars of F. occidentalis . In a previous study, we reported that these species effectively reduced F. occidentalis numbers in strawberry grown under controlled conditions (Rahman et al., 2011a). Moreover, multiple‐species releases of these predatory mites are more effective than single‐species releases (Rahman et al., 2011b).…”
Section: Introductionmentioning
confidence: 92%
“…On strawberries, T. montdorensis has been shown to reduce thrips numbers significantly more than N. cucumeris (Rahman et al 2011a(Rahman et al ,b,c, 2012.…”
Section: Wft Larval and Adult Foliage Predatorsmentioning
confidence: 99%
“…Comparisons between T. montdorensis and N. cucumeris found that both predatory mites reduced the numbers of thrips equally. On strawberries, T. montdorensis and N. cucumeris were also able to reduce thrips numbers similarly, although T. montdorensis was able to reduce WFT slightly more than N. cucumeris on occasion (Rahman et al 2011a(Rahman et al ,c, 2012. The biology of N. cucumeris and T. montdorensis is quite similar, but T. montdorensis has been shown to have a higher intrinsic rate of increase than N. cucumeris (Steiner et al 2003), and to consume more thrips larvae per day (Vanhouten et al 1995).…”
Section: Western Flower Thrips Biological Control Experimentsmentioning
confidence: 99%